2022
DOI: 10.1111/jgh.15964
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory role of basophils in oxazolone‐induced chronic intestinal inflammation

Abstract: Background and Aim:The functions of basophils have not been elucidated until recently because of their rarity. However, with recent developments in basophil-specific antibodies and basophil-deficient animals, the roles of basophils in various diseases related to chronic inflammation have been clarified. In this study, we aimed to investigate the roles of basophils in human ulcerative colitis (UC) and oxazolone (OXA) colitis using genetically engineered Mcpt8 DTR mice. Methods: Immunohistochemical staining of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Previous randomized controlled trials have reported that IBD is associated with high levels of lymphocyte counts, eosinophil counts, and basophil counts ( 36 38 ). However, there has been no evidence to support the causal connection between genetically predicted lymphocyte count, eosinophil count, and basophil count with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous randomized controlled trials have reported that IBD is associated with high levels of lymphocyte counts, eosinophil counts, and basophil counts ( 36 38 ). However, there has been no evidence to support the causal connection between genetically predicted lymphocyte count, eosinophil count, and basophil count with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…The robust basophil recruitment in acute colitis in AKR1B8 KO mice is potentially very interesting, since human IBD patients have increased basophils ( 43 45 ). Depletion of basophils by diphtheria toxin ameliorates the colonic inflammation in oxazolone-induced colitis in the Mcpt8 DTR mice model ( 43 ). Various cytokines and chemokines are reported to regulate the recruitment of basophils.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic basophil infiltration was significantly increased in patients with UC, and these seems to be related with their clinical manifestation; in fact, in murine OXA-induced colitis, a significant increase in basophil infiltration was observed, and when basophils were depleted by diphtheria toxin, inflammation improved significantly and mRNA expression of some proinflammatory cytokines, including TNF-α and IFN-γ, decreased significantly [45].…”
Section: Basophilsmentioning
confidence: 95%